2020
DOI: 10.1109/access.2020.2999562
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram Signal Eye Blink Rejection Improvement Based on the Hybrid Stone Blind Origin Separation and Particle Swarm Optimization Technique

Abstract: Electroencephalogram (EEG) extraction has widely used Stone's Blind Source Separation (Stone's BSS) algorithm. However, Stone's BSS algorithm is sensitive to the initial half-life (ℎlong, ℎshort) and weight vector W parameters, which affect the convergence of the algorithm. This paper proposes a hybridization of Stone's BSS with Particle Swarm Optimization (PSO) to boost the separation process. An improved Stone's BSS (ISBSS) method is employed to reject eye blinking from the electroencephalogram (EEG) mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In this study, present a new application for Stone's Blind Source Separation method in brain signal analysis to separate an EOG and power line noise artefacts from electroencephalogram (EEG) mixtures with PSO hybridization to enhance the separation process. We consider the algorithm suggested by the authors M. A. Ahmed, et al in [13] to evaluate the efficiency of the suggested method. The evolution of the method is based on the rejection of other artefacts, such as electrooculogram (EOG) and power line noise artefacts from the EEG mixture.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, present a new application for Stone's Blind Source Separation method in brain signal analysis to separate an EOG and power line noise artefacts from electroencephalogram (EEG) mixtures with PSO hybridization to enhance the separation process. We consider the algorithm suggested by the authors M. A. Ahmed, et al in [13] to evaluate the efficiency of the suggested method. The evolution of the method is based on the rejection of other artefacts, such as electrooculogram (EOG) and power line noise artefacts from the EEG mixture.…”
Section: Introductionmentioning
confidence: 99%